Study protocol for the ‘preventing functional decline in acutely hospitalised older patients (PREV_FUNC)’ study: effects of two multicomponent exercise programmes on physical function – a three-armed randomised controlled trial - Miia Kivipelto; Anne-Marie Boström; Maria Hagströmer; Anna-Karin Welmer; Christina Sandlund; Linda Sandberg; Caroline Björck; Julia Hamilton; Gunilla Helgstrand; Charlotte Lindgren; Linda Nordstrand; Petter Sandstedt (BMJ Open)
Introduction Acutely hospitalised older patients often live with frailty and have an increased risk of impaired physical function. Previous studies suggest that exercise might mitigate the risk of physical impairment; however, further research is needed to compare the effect of different types of exercise interventions. In this paper, we report a protocol for a trial that aims to examine (1) if multicomponent exercise interventions (interventions that include both mobility and strengthening exercises) have effects on physical function compared with usual care in older adults and (2) if a comprehensive multicomponent exercise programme is more effective than a simple multicomponent exercise programme that only include walking and sit-to-stand exercises.Methods and analysis This is a three-armed randomised controlled trial, with two intervention groups (comprehensive and simple exercise programme) and a control group receiving usual care. We will include 320 participants aged ≥75 years from geriatric medical departments of four hospitals in Stockholm, Sweden. Assessments will be conducted at hospital admission, discharge and 3 months thereafter concerning physical function (primary outcome), activities of daily living, health-related quality of life, sarcopenia and falls. The number of readmissions will be registered up to 1 year after discharge. Data will be analysed with linear mixed effects models, according to the intention-to-treat approach.Ethics and dissemination Ethical approval for this trial has been granted by the Swedish Ethical Review Authority (approval number 2022-03032-01). Data collection will consider the information requirement, the requirement of consent, confidentiality obligations and the utilisation requirement. Trial findings will be disseminated through multiple channels, including scientific publications and conferences, and workshops with healthcare professionals and the public.Trial registration number NCT05366075